Consensus Statement on Round Window Vibroplasty. (October 2014) - Beltrame, Achille M.; Todt, Ingo; Sprinzl, Georg; Profant, Milan; Schwab, Burkhard
Objective: This study aimed to review current knowledge regarding implantation of the Vibrant Soundbridge floating mass transducer (FMT) at the round window (round window vibroplasty) as well as to form a consensus on steps for a reliable, stable surgical procedure. Data Sources: Review of the literature and experimental observations by the authors. Conclusion: Round window (RW) vibroplasty has been established as a reliable procedure that produces good and stable results for patients with conductive or mixed hearing loss. The experience gained over the past few years of the authors' more than 200 implantations has led to consensus on several key points: (1) a wide and bloodless access to the middle ear with facial nerve monitoring, (2) the careful and correct identification and exposure of the round window membrane, (3) a good setup for efficient energy transition of the FMT, namely, perpendicular placement of the FMT with no contact to bone and the placement of cartilage behind the FMT to create a preloaded "spring" function, and (4) 4 points of FMT fixation: a rim of the round window bony overhang left intact both anterior and posterior to the FMT, conductor link stabilization, and cartilage behind the FMT. In addition, the FMT should be covered with soft tissue.